The evolutionary origin of moral agency and its implications for Ethics - Richart, Andrés (Pensamiento. Revista de Investigación e Información Filosófica, 2017)
Moral agency, understood as the faculty that enables morality, appears due to the psychobiological structures that set its conditions of possibility. We try to understand its evolutionary origin attending the possibility that moral agency emerged as an evolutionary by-product, with no specific function, it would be a result derived from the concurrence of other elements that emerged and developed itself adaptively. After that we will make some considerations regarding the scope of empirical science and ethics in relation to morality.
Keywords: adaptation; moral agency; spandrel; evolution; exaptation; by-product.